Modernization through dancing bodies in Turkey - Yüceil, Zeynep Günsür. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The present study aims to explore the first thirty years of State Ballet Institutions of Turkey. It was based primarily upon the oral interviews of Turkish ballet’s subjects and the critics’ reviews mostly published in journals and newspapers of the time. The study is divided into six chapters. An assessment of the foundation of institutional ballet in the world constitutes the first chapter. Chapter II is concerned with the dance scholarship in Turkey. Chapter III consists of two sections: The first one is based on a historical narrative related to the first state sponsored ballet institutions, namely the Ankara State Conservatory of Ballet and the Ankara State Ballet Company. The history of the foundation of the relevant educational framework combined with the professional company is explored through the readings and first hand witnesses’ memories. The second section of this chapter introduces the most significant actors of early Turkish ballet. The British teachers and choreographers as the initiators of ballet, Turkish bureaucrats as the representatives of the state and the first Turkish dancers as the pioneers of this art form have been presented. Chapter IV is concerned with the issues of institutionalization of Turkish ballet, followed by Chapter V which is involved with the debate on constructing ‘the national’. Different approaches were analyzed in relation to the presentations of the national. Finally, Chapter VI focuses on the individual stories as they are told by the first generations of the Turkish ballet artists. Their stories include gender perspectives, passion, frustration, and searching. Their memories are expressed as they are.|Keywords: Turkish ballet, institutionalization, modernization, memory, identity
Keywords: Ballet -- Turkey -- History.